2022
DOI: 10.1002/cbdv.202200485
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Curcumin Derivatives in Breast Cancer

Abstract: Curcumin is a potential plant-derived drug for the treatment of breast cancer. Poor solubility and bioavailability are the main factors that limit its clinical application. Various structural modification strategies have been developed to improve the anti-breast cancer activity of curcumin. This review focuses on the difference of modification sites and heterocyclic/non-heterocyclic modifications to systematically summarize curcumin derivatives with better anti-breast cancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…The results indicated that the inhibitory effect of desired CUR@ZIF-SF-PDA nanoparticles on the proliferation of MCF-7 and SK-BR-3 cells was correlated with DNA damage-induced G2/M phase arrest. This observation is in line with previous reports that CUR and its derivates demonstrated anti-cancer activity by increasing G2/M cell cycle arrest in various breast cancer cell lines, including T47D and MDA-MB-231 cells [94][95][96]. On the other hand, CUR and CUR-loaded nanoparticles treatments showed less effect on the cell cycle distribution of AD-293 human embryonic kidney cells (Figure 8f) compared with MCF-7 and SK-BR-3 breast cancer cells (Figure 8d,e), suggesting that desired nanoparticles induced less DNA damage on non-cancer cells than that on breast cancer cells in line with the MTT data above.…”
Section: Cell Cycle Analysissupporting
confidence: 92%
“…The results indicated that the inhibitory effect of desired CUR@ZIF-SF-PDA nanoparticles on the proliferation of MCF-7 and SK-BR-3 cells was correlated with DNA damage-induced G2/M phase arrest. This observation is in line with previous reports that CUR and its derivates demonstrated anti-cancer activity by increasing G2/M cell cycle arrest in various breast cancer cell lines, including T47D and MDA-MB-231 cells [94][95][96]. On the other hand, CUR and CUR-loaded nanoparticles treatments showed less effect on the cell cycle distribution of AD-293 human embryonic kidney cells (Figure 8f) compared with MCF-7 and SK-BR-3 breast cancer cells (Figure 8d,e), suggesting that desired nanoparticles induced less DNA damage on non-cancer cells than that on breast cancer cells in line with the MTT data above.…”
Section: Cell Cycle Analysissupporting
confidence: 92%
“…218 Many studies on different cancer treatments (both preclinical and clinical trials) have shown that CUR is a promising anticancer agent that can be used alone or in combination with other drugs. [219][220][221][222][223][224] However, CUR's clinical application in BC is constrained by its low bioavailability, poor water solubility, short halflife, fast metabolism, and inadequate tumor targeting capacity. Therefore, researchers have developed different drug delivery systems to address these problems, and great progress has been made in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is mainly used for treating cancer. ( Rajendran et al, 2022 ; Tang et al, 2022 ; Vadukoot et al, 2022 ; Wang et al, 2022 ; Yin et al, 2022 ). However, the anticancer activity of curcumin has not been fully elucidated in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%